Ethnomathematical Exploration of Tegal Traditional Food as Source of Contextual Problems in Problem-Based Learning Model - Fauziah, Salsa; Zaenuri, Zaenuri (Unnes Journal of Mathematics Education, 2025)
This study aims to explore the ethnomathematical values found in traditional foods of Tegal and to identify their potential as alternative sources of contextual problems in mathematics learning based on Problem Based Learning (PBL). The research employed a qualitative approach with an ethnographic method through literature review and visual observation using secondary documentation. Data were collected from various written sources and relevant images, then analyzed to reveal the geometric shapes and mathematical concepts embedded within them. The exploration results indicate that six types of traditional Tegal foods, namely tahu aci, bogis poci, olos, alu-alu, kamir, and apem, possess geometric forms that can be linked to concepts of solid geometry, plane geometry, and algebra. These findings provide a foundation for designing contextual problems aligned with the principles of PBL, where students are presented with real-world problems, work collaboratively, and construct meaningful understanding. This study does not measure learning effectiveness but produces a thick description that can serve as a reference for teachers and curriculum developers in integrating local wisdom into mathematics learning.